Republic of Azerbaijan : Technical Assistance Report-Government Finance Statistics Missions (May 17-21 and July 22-August 4, 2021). (IMF Staff Country Reports; Country Report, 2022)
Following the launch of the Caucasus, Central Asia, and Mongolia Regional Capacity Development Center (CCAMTAC) in February 2021, and in response to a request from the Azerbaijani authorities to support their statistical capacity development (CD) in government finance statistics (GFS), a series of technical assistance (TA) missions took place remotely (via Zoom meeting platform) during May 17-21 and July 22-August 4, 2021. Both missions were conducted by Mr. Roderick O'Mahony (GFS expert), who worked with the staff of the Ministry of Finance's Medium-Term Expenditure Framework (MTEF) Development Center as the main counterparts. He also met with other relevant agencies, including the State Oil Fund of the Republic of Azerbaijan (SOFAZ), the State Employment Agency, and the State Social Protection Fund.1